PENGARUH STRATEGI MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI DI SMA NEGERI 2 PAGUYAMAN - Murni Asih, Ni Made; Bumulo, Frahmawati; Sudirman, Sudirman; Bahsoan, Agil; Toralawe, Yulianti (Journal of Economic and Business Education, 2025)
The study aimed to determine whether there was an effect of teacher’s teaching strategies on students’ learning outcomes in the accounting subject. This study employed a descriptive-quantitative approach with a sample size of 31 people. The instruments used were questionnaires, whereas the data analysis technique used was simple linear regression analysis. The results of data analysis disclosed that there was a significant effect of teacher’s teaching strategies (47.3%) on students’ learning outcomes in the Accounting subject at SMA Negeri 2 Paguyaman. In the meantime, the remaining 52.7% was affected by other variables that not examined in this study,